Value-Added Products From Soil, Brown Coal, and Composted City Solid Waste - Eswaran, S. V. (Frontiers in Sustainable Food Systems, 2021)
This review article highlights alternative innovative uses of soil, brown coal and composted solid city waste. The latter lead to environmental pollution, which can be addressed by using these materials to generate value added products. Humic substances present in there can be isolated in large amounts and used in diverse fields like sustainable agriculture, horticulture, bio-medicine and materials science. These have been shown to be non-toxic, safe for humans and serve as growth promotants for plants and to cure stomach ailments. The recent discovery of their anti-viral/ anti HIV-AIDS activity is described here in some detail. The use of humic substances for making Dye Sensitised Solar Cells (DSSCs) and for preparing catalyst for reduction and for oxidation processes is also highlighted. Such innovative uses of humic substances can lead to environmental cleaning and positively impact climate change.